Ecología en el ‘De Genesi ad litteram libri XII’ - Weinberg, Heinrich (2022)
The article deals with Augustine’s De Genesi ad litteram. A brief presentation of the work, its chronology and contents is made, to later consider the ecological elements of the Work. First of all, the text of Wis 11:21 is approached, to emphasize that all creation has been the work of the Trinity, which acts in everything with a measure, a number and a weight. A brief presentation is made of the exegesis of Wis 11:21 in other works of St. Augustine, particularly De Genesi aduersus manicheos and the second book of De libero arbitrio. Subsequently, a reflection is made on the differences among the living beings that St. Augustine establishes within De Genesi ad litteram, in order to emphasize the superiority of the human being over creatures, as image and likeness of God, as well as the impossibility of the transmigration of the soul from a human being to an animal, or vice versa. The importance of the command given by God to man to cultivate and take care of the garden of Eden is emphasized, stressing the ecological elements of this command, as well as its ecological implications. The article shows how creation has a "sacramental" character, since the perfection, beauty and order of the Creator are embodied in all his creatures, as an invitation to discover the Creator through his creatures. The ideas presented in De Genesi ad litteram are also linked to other Augustinian works, especially the first commentaries on the Book of Genesis and some of Augustine’s early works.